Comprehensive subclasses of analytic functions and coefficient bounds - Serap Bulut (AIMS Mathematics, 2020)
In this paper, we introduce two general subclasses of analytic functions by means of the principle of subordination and investigate the coefficient bounds for functions in these classes. The well-known results are obtained as a corollary of our main results. Especially, we improve the results of Altıntaş and Kılıç [1].